Fakta dan Kebenaran Persfektif Filsafat Ilmu dalam Pengembangan Ekonomi Islam - Ali Wardani; Agustan Agustan; Reski Cahyani Ilham; Abdul Syatar (LABATILA : Jurnal Ilmu Ekonomi Islam, 2023)
There is a deep connection between Islamic economics and philosophy. Philosophy as the mother of knowledge contributes greatly in developing Islamic economics. This research method is qualitative literature (library research) using a narrative approach. The data collection techniques are orientation and exploration. The collected data then analyzed using inductive and deductive techniques. The results explain that philosophy plays a role in making the scope of Islamic economics that includes normative, positive and predictive knowledge. Predictive and positive have produced Islamic economic theories, while normative has given birth to other branches of Islamic economics such as muamalah, Islamic economic ethics, Islamic financial system, Islamic accounting, Islamic economic development, Islamic leadership management and zakat. As for the location of facts and truths from the perspective of the philosophy of science in development of Islamic economics, namely in positive knowledge that produces Islamic economic theory. However, Islamic economic theory must be empirically proven through a series of truth tests.